Analisis Pengembangan Ekonomi Hijau dengan Basis Pertanian dengan Implementasi Maqashid Syariah di Sumatera Utara - Nurul Annisa; Isnaini Harahap (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
North Sumatra is one of the provinces in Indonesia which has abundant natural resources. Due to the irreparable environmental damage that has occurred, several groups advocate and implement policies related to green economy, one of which is agriculture. To improve the health and productivity of agro-ecosystems organically and to provide sufficient, high-quality and long-lasting food and fiber supplies, organic farming systems are a comprehensive and integrated production approach. This study uses a literature review research method in a qualitative descriptive investigation. In an effort to advance its mission to promote environmentally friendly agriculture, the Ministry of Agriculture is currently researching and developing organic rice. One of them was developed in Deli Serdang by local farmers. Current trends show a shift in consumer tastes towards healthier choices. As a result of the existing challenges in obtaining public support, organic farming is still carried out on a small scale in the Deli Serdang area.Organic farming is a paradigm for advancing the overall goal of a green economy because organic farming is ecologically sound and financially profitable, and adheres to the economic principles of Maqasid Syariah. Keywords: Green Economy, Agriculture, Maqashid Sharia.